(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The list of the vascular plants of the projected landscape reserve «Lesovyy Canyon» includes 222 species of 155 genera, 52 families, 3 classis, 2 divisio. Among them 13 species included to the various Red Lists.